קולות מן המזרח: שירים יפניים בתרגום לאה גולדברג - כהן דורון ב'; כהן שירה מ' (מכאן, 2024)
Hebrew poet Lea Goldberg read poetry in ten languages or more and was attracted also to poetry in languages she could not read. Poetry, in any language and culture, clearly captivated her. She felt, moreover, a powerful urge to translate the poetry she appreciated into Hebrew as can be seen from her many translations, done mostly from Russian, German, Italian, French, and English. In addition she also rendered several dozen poems through relay translation, in particular Chinese and Japanese poems she read in German, English, or Russian translations. In this article, we give a concise overview of Goldberg’s relation to the cultures of East Asia, and focus on her translations of Japanese poems, while striving to identify both the translations she used and their Japanese originals. We found that while when translating directly, Goldberg took great care to maintain the original form, relay translation allowed her more freedom in creating a Hebrew poem while maintaining the spirit of the not directly experienced original.